Epithelial‐to‐Mesenchymal Transition Induced by TGF‐β1 Is Mediated by AP1‐Dependent EpCAM Expression in MCF‐7 Cells. Issue 4 (April 2015) - Gao, Jiujiao; Yan, Qiu; Wang, Jiao; Liu, Shuai; Yang, Xuesong
<x xml:space="preserve">Abstract</x> The epithelial‐to‐mesenchymal transition (EMT), a process involving the breakdown of cell–cell junctions and loss of epithelial polarity, is closely related to cancer metastasis and invasion. The epithelial cell adhesion molecule (EpCAM) is a type I transmembrane protein expressed in the majority of normal epithelial tissues and overexpressed in the majority of human epithelial cancers including breast cancer. EpCAM plays an important role in cancer progression. We showed that EpCAM participated in TGF‐β1‐induced EMT. TGF‐β1 treatment of MCF‐7 breast cancer cells was shown to induce EpCAM expression, which promoted the EMT and cell migration. EpCAM overexpression further enhanced TGF‐β1‐induced EMT and EpCAM knockdown inhibited TGF‐β1‐induced EMT. We further demonstrated that TGF‐β1 treatment induced the phosphorylation of JNK that was in turn responsible for the increased expression of Jun and Fos. This result suggests an important role of the JNK to AP‐1 signaling to EpCAM downstream of TGF‐β1 for the induction of EMT in the breast cancer cells. Collectively, our study highlights a novel function for EpCAM in TGF‐β1‐induced EMT process and suggests that targeting of EpCAM may be an attractive strategy to treat breast cancer. This study implicates the potential value of EpCAM as a molecular marker for breast cancer. J. Cell. Physiol. 230: 775–782, 2015. © 2014 Wiley Periodicals, Inc.